ANALISIS KOMPETENSI, BEBAN KERJA, DISIPLIN KERJA DAN LOYALITAS KARYAWAN - Joko Irawan; Nur Wening; Natalia Ika Eristaria (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2022)
The aims this study to analyse the competence, work load, work disiplince, and loyalty of permanent employees of conservation at Gembira Loka Zoo Yogyakarta type of the research is cuantitative descriptive research, the sampling technique of this reaearch is non probality sampling technique with the type of saturated sampling ( census ) of 36 respondent Whyle the analytical methode uses Descriptive Statistic by using means and mode analysis, the result of this study show that (1) the competence of permanent employees of conservation department at Gembira Looka Zoo Yogyakarta is in good criteria with a mean value of 3,99. (2) the work load of permanent employees of conservation department at Gembira Looka Zoo Yogyakarta is in good criteria with a mean value of 3,83. (3) the work diciplince of permanent employees of conservation department at Gembira Looka Zoo Yogyakarta is in good criteria with a mean value of 4,16. (4) the loyalty of permanent employees of conservation department at Gembira Looka Zoo Yogyakarta is in good criteria with a mean value of 4,15.